2021
DOI: 10.1037/cou0000553
|View full text |Cite
|
Sign up to set email alerts
|

Does peer relationship matter? A multilevel investigation of the effects of peer and supervisory relationships on group supervision outcomes.

Abstract: Research in clinical supervision has primarily focused on the contribution of supervisors to training outcome. However, peers may also play a significant role in trainees' development, particularly during group supervision. Fifty-three trainees from 10 supervision groups completed measures of peer relationship, supervisory working alliance (SWA), supervision satisfaction (SAT), and counseling self-efficacy (CSE) at three time points during a 20-week counseling practicum at a department clinic in Hong Kong. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 46 publications
(86 reference statements)
0
12
0
Order By: Relevance
“…This being said, it is important to note that the effect sizes for the mutual effects were both small (absolute values around .10). Thus the self-reinforcing force for the dynamic system was not strong (Li & Kivlighan, 2020), and many other factors could come into play to affect therapist self-efficacy (e.g., supervisory relationship, Chui et al, 2021) or client outcome (e.g., therapist helping skills, Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This being said, it is important to note that the effect sizes for the mutual effects were both small (absolute values around .10). Thus the self-reinforcing force for the dynamic system was not strong (Li & Kivlighan, 2020), and many other factors could come into play to affect therapist self-efficacy (e.g., supervisory relationship, Chui et al, 2021) or client outcome (e.g., therapist helping skills, Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the inclusion of peers in the supervision process supports novice supervisees in normalizing their anxiety and fears and developing their counseling self-efficacy (Atik & Erkan Atik, 2019;Borders & Brown, 2009;Mastoras & Andrews, 2011;Swank & McCarthy, 2015;Ülker Tümlü, 2019). In this sense, conducting supervision in the form of group supervision is very effective in improving the counseling selfefficacy of supervisees (Bakalım et al, 2018;Borders & Brown, 2009;Chui et al, 2021;Ivers et al, 2017;Tan & Chou, 2018). The current study revealed that both the experimental and comparison groups were effective in improving the counseling and meeting management skills of novice supervisors.…”
Section: Conclusion and Discussionmentioning
confidence: 57%
“…Nevertheless, supervisees feel secure in a supervision process focused on counseling performance skills, cognitive counseling skills, professional behavior, and self-awareness, their anxiety decreases, and their counseling self-efficacy improves (Ülker Tümlü, 2019). Moreover, group supervision can be very effective in improving the counseling self-efficacy of supervisees (Chui et al, 2021;Tan & Chou, 2018). In this process, supervisees' counseling self-efficacy improves through various ways, such as receiving and giving feedback from peers (Swank & McCarthy, 2015), normalizing anxiety (Mastoras & Andrews, 2011), receiving peer support and acquiring multiple perspectives (Atik & Erkan Atik, 2019).…”
Section: Counseling Self-efficacymentioning
confidence: 99%
See 2 more Smart Citations